Hydrogels with smart systems for delivery of hydrophobic drugs. (3rd July 2017) - Gu, Dunyin; O'Connor, Andrea J.; G.H. Qiao, Greg; Ladewig, Katharina
ABSTRACT: Introduction : Smart hydrogel systems present opportunities to not only provide hydrophobic molecule encapsulation capability but to also respond to specific delivery routes. Areas covered : An overview of the design principles, preparation methods and applications of hydrogel systems for delivery of hydrophobic drugs is given. It begins with a summary of the advantages of hydrogels as delivery vehicles over other approaches, particularly macromolecular nanocarriers, before proceeding to address the design and preparation strategies and chemistry involved, with a particular focus on the introduction of hydrophobic domains into (naturally) hydrophilic hydrogels. Finally, the applications in different delivery routes are discussed. Expert opinion : Modifications to conventional hydrogels can endow them with the capability to carry hydrophobic drugs but other functions as well, such as the improved mechanical stability, which is important for long-term in vivo residence and/or self-healing properties useful for injectable delivery pathways. These modifications harness hydrophobic-hydrophobic forces, physical interactions and inclusion complexes. The lack of in-depth understanding of these interactions, currently limits more delicate and application-oriented designs. Increased efforts are needed in (i) understanding the interplay of gel formation and simultaneous drug loading; (ii) improving hydrogel systems with respect to their biosafety; and (iii) control over release mechanism and profile.